CORPORATE SOCIAL RESPONSIBILITY COST AND FINANCIAL PERFORMANCE OF LISTED OIL AND GAS FIRMS IN NIGERIA - OFURUM, Clifford Obiyo; Ngoke, Obo-Sam (Archives of Business Research, 2022)
Despite the increasing pressures and agitations, the oil and gas firms operating in Nigeria have remained indifferent to the discharge of their corporate social responsibility, on the notion that it constitutes a drain on their financial position. This article investigates the relationship between the cost of corporate social responsibility and the financial performance of oil and gas companies listed in Nigeria. The study adopted a descriptive research design. Data for the Study obtained from secondary sources were analysed using Pearson Product Moment Correlation and Regression Statistical Techniques. HRDC, EPC and DCC were found to have positive relationships with the financial performance (ROA, ROE and NPM) of oil and gas companies listed in Nigeria. The study concludes that CSR costs are positively correlated with the financial performance of Nigerian-listed oil and gas companies. Therefore, the study recommends, among other things, that: (i) the costs associated with corporate social responsibility be increased by publicly traded oil and gas companies because it improves their financial performance. (ii)The necessary regulatory framework to improve cost-effectiveness and report all corporate social responsibility initiatives should be established. Keywords: Financial Performance, Corporate Social Responsibility, and Oil /Gas Firms.